Neurovascular responses to neuronal activity during sensory development - Konecny, Lukas; Quadir, Rafid; Ninan, Abel; Rodríguez-Contreras, Adrián (Frontiers in Cellular Neuroscience, 2022)
Understanding the development of intercellular communication in sensory regions is relevant to elucidate mechanisms of physiological and pathological responses to oxygen shortage in the newborn brain. Decades of studies in laboratory rodents show that neuronal activity impacts sensory maturation during two periods of postnatal development distinguished by the maturation of accessory structures at the sensory periphery. During the first of these developmental periods, angiogenesis is modulated by neuronal activity, and physiological levels of neuronal activity cause local tissue hypoxic events. This correlation suggests that neuronal activity is upstream of the production of angiogenic factors, a process that is mediated by intermittent hypoxia caused by neuronal oxygen consumption. In this perspective article we address three theoretical implications based on this hypothesis: first, that spontaneous activity of sensory neurons has properties that favor the generation of intermittent tissue hypoxia in neonate rodents; second, that intermittent hypoxia promotes the expression of hypoxia inducible transcription factors (HIFs) in sensory neurons and astrocytes; and third, that activity-dependent production of angiogenic factors is involved in pathological oxygen contexts.